Hyper-IgE Syndrome with STAT3 Mutation: A Case Report in Mainland China - Lixin Xie; Xiaoxiang Hu; Yang Li; Weihua Zhang; Liang'an Chen (Clinical and Developmental Immunology)
Hyper-immunoglobulin E syndromes (HIES) including compound primary immunodeficiency and nonimmunological abnormalities are characterized by extremely high serum IgE levels, eosinophilia, eczema, susceptibility to infections, distinctive facial appearance, retention of deciduous teeth, cyst-forming pneumonias, and skeletal abnormalities. Itis reported that some cases of familial HIES are relative to autosomal dominant or recessive inheritance, but most cases are sporadic, and result from mutations in the human signal transducer and activator of transcription 3 (STAT3) gene. In this paper, we firstly report a young man diagnosed of Hyper-IgE syndrome with STAT3 mutation in Mainland China, and investigate the autosomal dominant trait of his family members.